PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI INOVASI PENGELOLAAN SAMPAH: IMPLEMENTASI BUDIDAYA MAGGOT (BLACK SOLDIER FLY) DAN UPCYCLING DI DESA SURABAYA UTARA - Effendy, Michael; Jurnal Wicara; Rabi'ah, Putri; Ningsih, Tiara; Ashari, Triyas; Saputra, Arza; Luthfi, Muhamad; Ramdhani, Adelia; Hidayat, Sandra; Adhari, Aulia; Hariani, Rosa; Diswandi, Diswandi (Universitas Mataram, 2025)
Waste has become a serious issue in Indonesia, including in Surabaya Utara Village, East Lombok, where most household waste is still burned or openly dumped. To address this problem, the KKN PMD team from the University of Mataram carried out a socialization and training program on July 31, 2025, introducing two main innovations: Black Soldier Fly (BSF) maggot cultivation to process organic waste into nutritious animal feed, and the production of recycled pillows from plastic waste. The activity was attended by 22 participants and conducted through presentations, hands-on practice, and discussions. The results showed high enthusiasm from the community, with several participants expressing interest in developing these initiatives into small-scale businesses. This program not only raised awareness and improved waste management skills but also opened up new economic opportunities for the villagers, while supporting environmental cleanliness and the achievement of the Sustainable Development Goals (SDGs) at the village level.